2012
DOI: 10.1128/mcb.00761-12
|View full text |Cite
|
Sign up to set email alerts
|

The Rab GTPase-Activating Protein TBC1D4/AS160 Contains an Atypical Phosphotyrosine-Binding Domain That Interacts with Plasma Membrane Phospholipids To Facilitate GLUT4 Trafficking in Adipocytes

Abstract: The Rab GTPase-activating protein TBC1D4/AS160 regulates GLUT4 trafficking in adipocytes. Nonphosphorylated AS160 binds to GLUT4 vesicles and inhibits GLUT4 translocation, and AS160 phosphorylation overcomes this inhibitory effect. In the present study we detected several new functional features of AS160. The second phosphotyrosine-binding domain in AS160 encodes a phospholipid-binding domain that facilitates plasma membrane (PM) targeting of AS160, and this function is conserved in other related RabGAP/Tre-2/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
53
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 46 publications
3
53
0
Order By: Relevance
“…We demonstrated that Akt provides the fidelity of spatial release of GLUT4 on the cell surface, and our findings support previous work that Akt signaling at the plasma membrane is required for the last step of GLUT4 exocytosis (Koumanov et al, 2005). Moreover, a downstream target of Akt, AS160, is mobilized to the plasma membrane and regulates GLUT4 vesicle exocytosis (Tan et al, 2012). Therefore, it is conceivable that locally activated Akt might recruit AS160 and its downstream Rab proteins, as well as the exocyst complex (Chen et al, 2011), to control the spatial release of GLUT4 into the plasma membrane.…”
Section: Discussionsupporting
confidence: 78%
“…We demonstrated that Akt provides the fidelity of spatial release of GLUT4 on the cell surface, and our findings support previous work that Akt signaling at the plasma membrane is required for the last step of GLUT4 exocytosis (Koumanov et al, 2005). Moreover, a downstream target of Akt, AS160, is mobilized to the plasma membrane and regulates GLUT4 vesicle exocytosis (Tan et al, 2012). Therefore, it is conceivable that locally activated Akt might recruit AS160 and its downstream Rab proteins, as well as the exocyst complex (Chen et al, 2011), to control the spatial release of GLUT4 into the plasma membrane.…”
Section: Discussionsupporting
confidence: 78%
“…So far, Rab2, Rab8b, Rab10, and Rab14 have been identified as substrates for recombinant GAP domains of TBC1D1 and TBC1D4 in vitro (4,16), but the significance of these findings for GLUT4 translocation in adipose and muscle cells in vivo remains to be further investigated. Moreover, the phosphotyrosine-binding domains may also be involved in TBC1D1/TBC1D4 signaling (17)(18)(19). Previous studies of isolated L6 muscle cells and 3L3-L1 adipocytes demonstrated that ablation of either Tbc1d1 or Tbc1d4, or overexpression of mutated proteins, resulted in reduced insulin-stimulated translocation of GLUT4 (20)(21)(22).…”
mentioning
confidence: 99%
“…The suggested mechanism for TBC1D1 regulation is primarily based on the wellknown regulation of its close homolog AS160. TBC1D1 interacts with IRAP (18), inactivates the same Rabs as AS160 (13), and binds 14-3-3 upon phosphorylation (16,19). Although Akt mediates AS160 phosphorylation on the crucial 14-3-3 binding sites, linking AS160 to insulin signaling, TBC1D1 binds 14-3-3 in response to AMPK activation, a kinase activated by exercise (2).…”
Section: /2mentioning
confidence: 99%